The year in cardiology: aorta and peripheral circulation: The year in cardiology 2019. (6th January 2020) - Heiss, Christian; Pitcher, Alex; Belch, Jill J F; De Carlo, Marco; Reinecke, Holger; Baumgartner, Iris; Mazzolai, Lucia; Aboyans, Victor
Abstract: